2014
DOI: 10.5455/jice.20140123040224
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity enhancement in MDA-MB-231 cells by the combination treatment of tetrahydropalmatine and berberine derived from Corydalis yanhusuo W. T. Wang

Abstract: Aim:Our previous works have demonstrated that Chinese herb medicine yanhusuo (Corydalis yanhusuo W. T. Wang) has strong anti-cancer proliferation effect in MDA-MB-231 cells. The goal of this study was to find out the synergic cytotoxicity effect of three natural compounds, tetrahydropalmatine (THP), berberine (Ber), and dehydrocorydaline (DHC), isolated from C. yanhusuo W. T. Wang.Materials and Methods:The IC50 of THP Ber and DHC in single use, as well as in combination use at fixed ratios and doses was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…However, treatment with both phenformin and BPTES yielded significant impacts on cellular viability, with LKB1-deficient cell lines being most sensitive (Figure 5D). Combination index and coefficient of drug interaction (CDI) were calculated to assess potential synergistic effects of phenformin and BPTES on cell viability, where CDI <0.7 indicates a significant synergy (Zhao et al, 2014). Strikingly, we observed that combination treatment with phenformin and BPTES yielded a synergistic response more so in LKB1-deficient cells (Figure 5E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, treatment with both phenformin and BPTES yielded significant impacts on cellular viability, with LKB1-deficient cell lines being most sensitive (Figure 5D). Combination index and coefficient of drug interaction (CDI) were calculated to assess potential synergistic effects of phenformin and BPTES on cell viability, where CDI <0.7 indicates a significant synergy (Zhao et al, 2014). Strikingly, we observed that combination treatment with phenformin and BPTES yielded a synergistic response more so in LKB1-deficient cells (Figure 5E).…”
Section: Resultsmentioning
confidence: 99%
“…Given the decreased plasticity of LKB1-deficient cells, we investigated whether combination treatments using phenformin and a glutaminase inhibitor would enhance the cell-killing effects in these cell populations. We observed that BPTES and phenformin synergistically decreased NSCLC cell survival, as evidenced by coefficient of drug interaction (CDI) scores <0.7 in A549 and H460 cell lines (Zhao et al, 2014). Strikingly, LKB1-deficient A549 and H460 cells were significantly more sensitive to combination treatment with phenformin and BPTES compared to LKB1-proficient cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lin et al confirmed that tetrahydropalmatine is the primary ingredient of Corydalis Rhizoma . Importantly, tetrahydropalmatine has anti‐MDR effect on MCF‐7 cell lines, and could enhance the ability to inhibit the proliferation of human leukemia cell lines by combining with vincristine . Another 11 medicines show similar effects.…”
Section: Introductionmentioning
confidence: 99%